Anti-Muslim Discrimination in France: Evidence from a Field Experiment - Marie-Anne Valfort (Institute of Labor Economics (IZA), 2018)
Relying on a correspondence study conducted in France before the 2015 attacks, this paper compares the callback rates of immigrants of Muslim and Christian culture who originate from the same country and whose religiosity varies from non-religious to religious. Based on responses to over 6,200 job ads, the results reveal an insignificant disadvantage for Muslims when they are not religious. However, Muslims lose further ground when they are religious, while the reverse occurs for Christians. Consequently, religious Muslims must submit twice as many applications as religious Christians before being called back by the recruiters. A follow-up survey confirms that the signal used to convey fictitious applicants' religiosity is not only viewed as relevant but that it is also correctly interpreted by employers.
Keywords: C93; J15; J71; Z12; 330; religion; religiosity; Islam; discrimination; France; correspondence study